2018
DOI: 10.1016/j.evalprogplan.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework for evaluating health equity promotion within community-based participatory research partnerships

Abstract: Community-based participatory research (CBPR) approaches present strong opportunities to promote health equity by improving health within low-income communities and communities of color. CBPR principles and evaluation frameworks highlight an emphasis on equitable group dynamics (e.g., shared leadership and power, participatory decision-making, two-way open communication) that promote both equitable processes within partnerships and health equity in the communities with whom they engage. The development of an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 29 publications
1
60
0
10
Order By: Relevance
“…Trust has been identified previously as a key indicator for the success of community-engaged partnerships in general 101 and for promoting health equity in particular. 102 Trust may be established through a commitment to longterm partnership processes that are mutually beneficial to community and academic partners. 103 Trust is also an important contextual factor for research participation, especially the contextual legacy of unethical and criminal research behaviors in the past that targeted racial and ethnic minority participants and communities.…”
Section: Discussionmentioning
confidence: 99%
“…Trust has been identified previously as a key indicator for the success of community-engaged partnerships in general 101 and for promoting health equity in particular. 102 Trust may be established through a commitment to longterm partnership processes that are mutually beneficial to community and academic partners. 103 Trust is also an important contextual factor for research participation, especially the contextual legacy of unethical and criminal research behaviors in the past that targeted racial and ethnic minority participants and communities.…”
Section: Discussionmentioning
confidence: 99%
“…This review found 55 reviews reporting evidence of different outcomes (Ortiz et al, 2020). The importance of conceptual models has also grown in terms of identifying theories of change and pathways of practices contributing to outcomes (Eder et al, 2013;Greenhalgh et al, 2016;Jagosh et al, 2012;Oetzel et al, 2018;Ward et al, 2018).…”
Section: Journal Of Participatory Research Methodsmentioning
confidence: 99%
“…C) PAR also rejects objectivist assumptions that distance the researcher and the participants from one another [121,123]. The close proximity of working can promote inclusion and confront engrained stigma and prejudices [32,120,124]. In line with the contact hypothesis [125] and social contact theory [125,126], positive contact between service-users, health professionals and others within the health system, e.g.…”
Section: Designmentioning
confidence: 98%
“…These drawbacks may be minimized through the emancipatory and critical theoretical foundation of PAR that seeks to explicitly and intentionally work with a range of stakeholders, including those historically oppressed, disempowered, vulnerable and marginalized groups (e.g., service-users) [62,107,112]. The participatory commitment of PAR provides space for diverse forms of expertise and promotes understanding of the different life-worlds of participants [32,87,120]. Working in a collaborative and non-hierarchical manner may facilitate deeper understanding of how implementation can be achieved [56,84,100,112,121].…”
Section: Designmentioning
confidence: 99%